Edukasi Tentang Skrining Kanker Serviks dengan Metode IVA Test - Ramah Hayu; Fanny Jesica (I-Com: Indonesian Community Journal, 2024)
Cervical cancer is one of the most common cancers in women and poses a serious threat to women worldwide. The incidence and mortality rate of cervical cancer in women is quite high and is expected to continue to increase. Cervical cancer is a cancer that occurs in the female reproductive organs. This disease occurs in women of childbearing age between the ages of 20 and 35 years. The purpose of this activity is to expand knowledge about the community through education. This activity begins by asking the mother's knowledge about cervical cancer screening. Furthermore, material transfer was carried out through Power Point and distribution of brochures. All mothers were enthusiastic about participating in this campaign, as evidenced by the many questions asked by the mothers. This activity was effective in improving the mothers' knowledge; it was seen that the mothers' understanding increased before and after the consultation, as evidenced by some of the questions that the mothers were able to answer. This action is the first step to improve mothers' knowledge about cervical cancer screening through VIA test